Os mitos de Espártaco - Silva, Neemias Oliveira da (2018)
This thesis proposes the investigation of the myth built regarding Spartacus figure, slaves revolution leader in Ancient Rome and the demystification of this character in contemporaneity. We also analyzed Spartacus uses and appropriations which from eighteenth century on became symbol of revolutions. Thus, Spartacus became part of the popular culture along the time, reviving the epic hero at the cinematographic work from Stanley Kubrick (1960). Resuming in the twenty-first century through the series Spartacus (2010 - 2013), from epic hero to hero of masses. The return of the mythic hero is seen as nostalgia, a hero's model that no longer exists. Based on this we studied how the cultural industry reinforces occidental beauty patterns based on a body model. The hero's body is muscled, considered virility synonym and sexual symbol. Technological and scientific advances contributed to disenchantment of myths, the super natural, demystifying the hero. New hero models were built, ordered and integrated to a globalized media. This way the sources analyzed were Spartacus series, classical and reference works. The methodology used consists on Spartacus iconography analysis as a cultural representative and product of mass culture. At last the fact that Spartacus series was chosen as audio visual source is justified by the symbolic form the body and hero are described as simulacra of contemporaneous man. Spartacus would unfold himself in his lots of myths: “Myths of Spartacus”